REFLECTIVE THINKING PRACTICE: AN ANALYSIS OF ENGLISH TEACHERS’ PERCEPTION DURING ONLINE LEARNING - Sugita, N.P.A.N; Myartawan, I.P.N.; Wahyuni, L.G.E (Universitas Pendidikan Ganesha, 2021)
Teachers face the challenge of creating quality learning. However, teachers have difficulty in designing online learning. This study aims to analyze the level of reflective thinking practice of English teachers during online learning. This research is a qualitative descriptive study. The subjects of this study were three English teachers. The methods used to collect data are questionnaires, observations, and interviews. Self-rated guideline questionnaires and interviews were used as research instruments. The research findings show that English teachers are categorized as advanced teachers and tend to use four reflective thinking skills in their teaching: lifelong learning skills, self-assessment skills, self-confidence skills, and self-assessment skills. They are teaching awareness. The English teachers feel that they must find the most effective strategies to improve their teaching. Teachers are aware of their strengths and weaknesses in teaching and believe that they can meet their needs as teachers in improving the quality of their teaching. Finally, the teachers try what they do to students according to their discipline to carry out the learning process according to the needs of students.